2018
DOI: 10.1007/s13205-018-1208-0
|View full text |Cite
|
Sign up to set email alerts
|

Fish trypsins: potential applications in biomedicine and prospects for production

Abstract: In fishes, trypsins are adapted to different environmental conditions, and the biochemical and kinetic properties of a broad variety of native isoforms have been studied. Proteolytic enzymes remain in high demand in the detergent, food, and feed industries; however, our analysis of the literature showed that, in the last decade, some fish trypsins have been studied for the synthesis of industrial peptides and for specific biomedical uses as antipathogenic agents against viruses and bacteria, which have been re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 106 publications
(146 reference statements)
1
9
0
Order By: Relevance
“…Accordingly, alkaline protease activity of L. peru presented the maximum value at pH 6, which has not been previously reported in lutjanid species, while the pH range of chymotrypsin activity in mammals and most aquatic organisms is 7.5-9.0 (Zhou et al 2011). On the contrary, the optimum pH of trypsin was found at pH 9, according to many other fish trypsin, ranging between 7 to 11 and stable at alkaline pH (7 to 9) (Jesúsde la Cruz et al 2018). However, optimum pH found in total alkaline proteases seems to be more influenced by the chymotrypsin activity and LAP rather than trypsinlike enzymes, supported by pH optimums found in chymotrypsin (pH 5) and LAP (pH 6 and 9) (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, alkaline protease activity of L. peru presented the maximum value at pH 6, which has not been previously reported in lutjanid species, while the pH range of chymotrypsin activity in mammals and most aquatic organisms is 7.5-9.0 (Zhou et al 2011). On the contrary, the optimum pH of trypsin was found at pH 9, according to many other fish trypsin, ranging between 7 to 11 and stable at alkaline pH (7 to 9) (Jesúsde la Cruz et al 2018). However, optimum pH found in total alkaline proteases seems to be more influenced by the chymotrypsin activity and LAP rather than trypsinlike enzymes, supported by pH optimums found in chymotrypsin (pH 5) and LAP (pH 6 and 9) (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Such phenomena of drastic reductions in muscle content result in a drop in quality and subsequent losses in the aquaculture industry. Serine proteases such as trypsin and trypsin‐like proteases are known to digest and hydrolyse muscles and collagens in aquatic species 84 . By combining data from the hepatopancreatic transcriptomic profiles of P .…”
Section: Functional Categories Of Transcriptomics In Portunid Crabsmentioning
confidence: 99%
“…In spite of this, it was considered that the best resulting mutant was the one that combines a long lasting high proteolytic activity (one single mutation provided around 25 times more proteolytic stability) with thermal instability, because the latter allows a tighter control of the enzymatic activity during biomedical application ( Olivera-Nappa et al 2013 ) . However, others have proposed that the thermal instability of cold-adapted trypsins represents a drawback for their practical use, taking also into consideration the prospects for its production ( de la Cruz et al 2018 ). In the case of the krill enzyme, an analysis of a structural model suggested that two residues of loop D (analogous to the autolysis loop of trypsins) might be targets for autolysis and thus, changes were incorporated at these positions; the mutant was more stable against autolysis than the wild-type form of the enzyme during the production of the recombinant ( Gudmundsdóttir & Pálsdóttir 2005 ).…”
Section: Crustacean Proteases and Their Debridement Potentialmentioning
confidence: 99%
“…Proteases are the largest group of industrial enzymes and have a variety of applications ranging from use in detergents, leather preparation and food processing. During the last decade, marine proteases of non-microbial origin have been assessed for different applications, such as the use of fish ( Klomklao 2008 ; Shahidi & Kamil 2001 ; Jesus de la Cruz et al 2018 ) and crustacean ( Rossano et al 2011 ) digestive proteases in the food industry. Conversely, digestive proteases from marine organisms have been less applied to the biomedical field.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation